2018
DOI: 10.5194/bg-15-1969-2018
|View full text |Cite
|
Sign up to set email alerts
|

Substrate potential of last interglacial to Holocene permafrost organic matter for future microbial greenhouse gas production

Abstract: Abstract. In this study the organic matter (OM) in several permafrost cores from Bol'shoy Lyakhovsky Island in NE Siberia was investigated. In the context of the observed global warming the aim was to evaluate the potential of freeze-locked OM from different depositional ages to act as a substrate provider for microbial production of greenhouse gases from thawing permafrost. To assess this potential, the concentrations of free and bound acetate, which form an appropriate substrate for methanogenesis, were dete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 96 publications
1
29
0
Order By: Relevance
“…However, owing to the high ice content, yedoma deposits are highly susceptible to warming-induced environmental changes, erosion, and ground subsidence following permafrost thaw (e.g., Morgenstern et al, 2013). Only 30 % of the yedoma region (about 416 000 km 2 ) is considered intact, while the other 70 % has already undergone some level of permafrost degradation (Strauss et al, 2013). Today, the whole yedoma domain stores 213-456 Pg of OC, of which 83-269 Pg is stored in intact yedoma and 169-240 Pg in thermokarst and refrozen taberal deposits (Zimov et al, 2006;Strauss et al, 2013Strauss et al, , 2017Hugelius et al, 2014;Walter Anthony et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, owing to the high ice content, yedoma deposits are highly susceptible to warming-induced environmental changes, erosion, and ground subsidence following permafrost thaw (e.g., Morgenstern et al, 2013). Only 30 % of the yedoma region (about 416 000 km 2 ) is considered intact, while the other 70 % has already undergone some level of permafrost degradation (Strauss et al, 2013). Today, the whole yedoma domain stores 213-456 Pg of OC, of which 83-269 Pg is stored in intact yedoma and 169-240 Pg in thermokarst and refrozen taberal deposits (Zimov et al, 2006;Strauss et al, 2013Strauss et al, , 2017Hugelius et al, 2014;Walter Anthony et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Only 30 % of the yedoma region (about 416 000 km 2 ) is considered intact, while the other 70 % has already undergone some level of permafrost degradation (Strauss et al, 2013). Today, the whole yedoma domain stores 213-456 Pg of OC, of which 83-269 Pg is stored in intact yedoma and 169-240 Pg in thermokarst and refrozen taberal deposits (Zimov et al, 2006;Strauss et al, 2013Strauss et al, , 2017Hugelius et al, 2014;Walter Anthony et al, 2014). For an about 88 000 km 2 area along the Bolshaya Chukochya and Alazeya River basins and the eastern parts of the Yana-Indigirka and Kolyma lowlands in northeastern Siberia, Shmelev et al (2017) estimate the size of the total carbon pool in the upper 25 m to be 31.2 Pg, of which 3.7 Pg is stored in yedoma deposits.…”
Section: Introductionmentioning
confidence: 99%
“…Previous permafrost research on the Bykovsky Peninsula included cryostratigraphical and cryolithological research on Yedoma and thermokarst-affected deposits (Kunitsky, 1989;Slagoda, 1993;Schirrmeister et al, 2002aSchirrmeister et al, ,b, 2018Slagoda, 2004Slagoda, , 2005Grosse et al, 2007;Romankevich et al, 2017;Ulyantsev et al, 2017). The total organic carbon (TOC) content of Yedoma deposits on the east coast of the Bykovsky Peninsula (Mamontovy Khayata) ranges from 2 to 14 wt%, whereas Holocene cover deposits on top of the Yedoma have a TOC between 2 and 27 wt% (Schirrmeister et al, 2002a).…”
Section: Study Areamentioning
confidence: 99%
“…A first estimate of the taberal deposit OC pools suggests ∼114 Gt OC, which is about 25% of the Yedoma domain OC storage (∼398 Gt) (Walter Anthony et al, 2014;Strauss et al, 2017). In several studies, it is also shown that the OM degradability in Yedoma deposits is higher compared to that in Holocene deposits (Knoblauch et al, 2013;Strauss et al, 2015;Jongejans et al, 2018;Stapel et al, 2018). However, the fate of OM in Yedoma deposits affected by thawing and subsequent qualitative and quantitative changes is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation